Comparing Human Factors for Augmented Reality Supported Single-User and Collaborative Repair Operations of Industrial Robots - Aschenbrenner, Doris; Leutert, Florian; Çençen, Argun; Verlinden, Jouke; Schilling, Klaus; Latoschik, Marc; Lukosch, Stephan (Frontiers in Robotics and AI, 2019)
In order to support the decision-making of industry partners within the upcoming discussions of how to use Augmented Reality in production, this article analyzes three user studies with overall 160 participants who perform the same repair task on a switch cabinet of an industrial robot. The studies compare different Augmented Reality instruction applications on different devices (head-mounted display, handheld tablet pc and projection-based spatial augmented reality) with baseline conditions (paper instructions and phone support) both in single and cooperative setting. Next to several indications about the performance of the individual device types for the single mode operation, the study can clearly show the significant superiority of using AR within the cooperative setting.